ANALISIS KEBIASAAN GEMAR MEMBACA PADA SISWA KELAS 3 SD DI UPT SD NEGERI 49 GRESIK - Eka Melavenia Nagata; Nanang Khoirul Umam (JUSEDA, 2022)
Reading is a versatile skill which is not only a basic tool for acquiring knowledge, but also influences people totally on individual and social terms. Elementary school students are children who are still underage, so there needs to be special monitoring from teachers and parents so that they enjoy reading. This study aims to determine the activities of fond of reading, supporting and inhibiting factors of fond of reading, as well as solutions that can increase students' interest in reading in grade 3 SD at UPT SD Negeri 49 Gresik. This study used a qualitative descriptive method with interview techniques with teachers, observations in the UPT SD Negeri 49 Gresik environment. The population in this study were Grade 3 UPT SD Negeri 49 Gresik students. Data collection techniques in this study were carried out through questionnaires, interviews and observation. The research design conducted by researchers is using a case study research design. Based on the results of the study, it was shown that grade 3 students had a high interest in reading if it was done in school facilities such as the school library room, school gazebo and other school facilities except in the classroom. Factors that influence students not to like reading in class are students feel bored when they have to read in class, books in class are less varied than books in the library, the atmosphere in class is not as comfortable when reading outside class as in library, in the school gazebo. The solution that must be taken by the teacher is to continue to direct students to read in the classroom, creating a special room for reading in the classroom. It is intended that students are more fond of reading in class and increase students' interest in reading during class hours, not only during breaks. However, this still needs special attention from the teacher to further increase reading activities so that it is evenly distributed among all students at school and the role of parents when students are out of school (home).